PERFORMANCE MODEL: Satisfaction, Commitment and Reward Based - Nurlaila, Putri (Sekolah Menengah Kejuruan (SMK) Pustek, 2022)
Performance is considered important, because for a company performance means achieving targets, increasing sales, increasing profits, advancing the company, and so on. Aware of the need for performance, the company seeks to maximize the factors that influence it, including increasing satisfaction, work commitment, and compensation. Departing from this phenomenon, this study tries to look at the probability of job satisfaction factors on increasing performance. The method used is quantitative with the number of respondents as many as 92 employees. The data sources are employees of PT. IKAD through a simple random sample technique. The results of the research show that the estimation value is either simultaneous or partial, that the best model in improving performance is to grow job satisfaction. However, self-satisfaction will be born if the company can provide good compensation.